2014
DOI: 10.1068/d4913p
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Places: The Inalienable Nature of Belonging in Place

Abstract: This paper focuses on the importance of historic, social, and material connections in belonging to place. Mauss's anthropological concept of a 'gift' is deployed to understand how places are cared for by a community over time. The development of tangible and intangible connections between past, present, and future people and places is explored. On the basis of in-depth, qualitative research with a group of people who have long-standing connections to their local place, memories and life-narratives are unravell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 41 publications
0
53
0
11
Order By: Relevance
“…27 Bennett refers to this form of belonging as 'ontological' belonging or 'being in this world'. 28 Perhaps this perspective does not feature prominently in the research literature on the urban middle class because these studies tend to focus on residents moving into the city and into neighbourhoods in the early stages of their working career and life course, 29 thereby highlighting strategic and conscious decision-making processes rather than the everyday and often unconscious process of making the neighbourhood one's home.…”
Section: Middle-class Belongingmentioning
confidence: 99%
“…27 Bennett refers to this form of belonging as 'ontological' belonging or 'being in this world'. 28 Perhaps this perspective does not feature prominently in the research literature on the urban middle class because these studies tend to focus on residents moving into the city and into neighbourhoods in the early stages of their working career and life course, 29 thereby highlighting strategic and conscious decision-making processes rather than the everyday and often unconscious process of making the neighbourhood one's home.…”
Section: Middle-class Belongingmentioning
confidence: 99%
“…On a slighter scale, attachment to one's neighbourhood is connected with fewer perceived rudeness (e.g., drug dealing, gang activity, traffic, etc.) on one's block and less fear of neighbourhood crime (Brown et al, 2003; Scannell & Gifford, 2010).According to Bennett (2014), 'belonging' is a hazy term that is yet but central to the character and everyday life of people. History, people, and place are the three bases of belonging (Bennett, 2014;Miller, 2003).…”
mentioning
confidence: 99%
“…History, people, and place are the three bases of belonging (Bennett, 2014;Miller, 2003). Belonging can be verbalised regarding "multiple social relationships broadening between past, present, and future generations and places" (Bennett, 2014, p. 658).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This statement is supported by the experience of Middle Eastern women in this study who reported that their sense of belonging was achieved by finding familiar spaces in their new habitat. Furthermore, this reproduction of history contributing to a sense of belonging aligns with Bennett (2014) As "an affective bond that connects people to places" (Lewicka 2013 family roots, and so on), although the process of forming emotional bonds with places requires further investigation. Lewicka (2014) states that declarative semantic memory (long-term factual stored information) could be an enabler in the process of an affective bond for a newcomer in a place.…”
Section: Theme 3: Sense Of Belongingmentioning
confidence: 99%